La volaille en région Centre-Val de Loire du Néolithique à nos jours. Approche archéozoologique - Colin Duval; Grégory Bayle; Séverine Braguier; Olivier Cotté; Alexandre Fontaine; Chloé Genies; Frédéric Poupon; Julie Rivière; Marilyne Salin; Marie-Pierre Horard-Herbin (Revue Archéologique du Centre de la France)
The multidisciplinary research programme of regional interest, VOLAILLES, from 2018, has in particular made it possible to carry out an exhaustive collection of archaeozoological data produced in the Centre-Val de Loire region for almost 60 years. The information gathered concerns 282 archaeological sites and covers a period from Prehistory to the present day. Within the framework of this project, it has made it possible to establish a detailed map of the distribution of the various farmyard birds over time, but above all to define the precise dynamics of the introduction and spread of domestic fowl, goose, duck, pigeon, turkey and peacock within the region and over the long term. This unprecedented study also made it possible to synthesise morphological data, drawn from bone measurements of the domestic fowl, and to take stock of knowledge on poultry on a French and European scale.